The Effect of Magnesium and Vitamin E Co-Supplementation on Glycemic Control and Markers of Cardio-Metabolic Risk in Women with Polycystic Ovary Syndrome: A Randomized, Double-Blind, Placebo-Controlled Trial - Jamilian, Mehri; Sabzevar, Niloufar Kazemi; Asemi, Zatollah (Hormone and Metabolic Research, 2018)
Data on the effects of magnesium and vitamin E co-supplementation on glycemic control and markers of cardio-metabolic risk of patients with polycystic ovary syndrome (PCOS) were collected. This investigation was conducted to evaluate the effects of magnesium and vitamin E co-supplementation on glycemic control and markers of cardio-metabolic risk in women with PCOS. This randomized, double-blind, placebo-controlled trial was carried out on 60 women with PCOS, aged 18–40 years old. Participants were randomly divided into two groups to receive 250 mg/day magnesium plus 400 mg/day vitamin E supplements or placebo (n=30 each group) for 12 weeks. Fasting blood samples were taken at baseline and after the 12-week intervention to quantify related variables. After the 12-week intervention, compared with the placebo, magnesium and vitamin E co-supplementation led to a significant reduction in serum insulin levels (–1.1±3.0 vs. +1.6±3.7 μIU/ml, p=0.003) and homeostatic model of assessment for insulin resistance (–0.2±0.7 vs. +0.4±0.9, p=0.002), and a significant increase in the quantitative insulin sensitivity check index (+0.01±0.01 vs. –0.009±0.02, p=0.003). Furthermore, magnesium plus vitamin E supplementation significantly decreased serum triglycerides (–15.0±24.4 vs. +6.7±22.2 mg/dl, p=0.001) and VLDL-cholesterol concentrations (–3.0±4.9 vs. +0.6±2.4 mg/dl, P=0.01) compared with the placebo. A trend toward a greater decrease in total cholesterol levels was observed in magnesium plus vitamin E group compared to placebo group (–7.0±32.6 vs. +8.1±26.6 mg/dl, p=0.05). In conclusion, magnesium and vitamin E co-supplementation for 12 weeks to PCOS women had beneficial effects on parameters of insulin metabolism and few markers of cardio-metabolic risk.
Keywords: magnesium; vitamin E; supplementation; polycystic ovary syndrome; glucose metabolism; lipid concentrations